Penerapan Motode Modelling Pada Kasus Intellectual Disability - Mohamad Putra Fadhiila Raistyanto Fadhiila Raistyanto; Yoga Prihatin; Rahmad A. Nugroho (Cakrawala: Jurnal Pendidikan, 2020)
Children with Down Syndrome experience developmental delays globally in gross and fine motor skills. This motor delay is accompaniedby mild to moderate Intellectual Disability with a majority IQ between 40 and 70.Miller and Chapman (1984) in Paul & Norbury (2012)estimate that nearly 50% of children with non-specific intellectual disabilities have language skills equivalent to their nonverbal abilities. .The rest have language skills that are not commensurate with their nonverbal abilities, namely 25% have a relative expressive languagedeficit. Speech therapist has a role in handling cases of Intellectual Disability in language skills. Therapeutic planning that is set on theclient in the form of a short-term goal is to improve receptive language skills at the level of the family category noun with an accuracy levelof 50% for 3 consecutive sessions and the therapy material given to the client is the exercise of pointing at family photos, namely: nizam,mother, ladies and gentlemen. This study aims to determine the description of the Intellectual Disability case at the Tugurejo HospitalSemarang, to find out the description of therapy planning in the Intellectual Disability case at the Tugurejo Hospital Semarang, todetermine the factors that influence the management of Speech Therapy in the Intellectual Disability case at the Tugurejo HospitalSemarang. The results of therapy on the ability to understand the family category as many as 5 meetings for 5 weeks with an accuracylevel of 80% have increased even though they have not been able to be consistent for 3 consecutive sessions. After 5 sessions of therapy, itcan be seen that the specified short-term goals have not been achieved because they are influenced by several factors, namely the age of theclient who is 6 years old and the client's poor attention